METODOLOGI AREA FRAME UNTUK PENGUKURAN PRODUKTIVITAS PADI DI KABUPATEN GARUT - Chafid, Mohammad (Informatika Pertanian, 2015)
The statistical method for measuring rice productivity by the CBS is based on sample frame of households. At the implementation of this method, problems were encountered in terms of accuracy in the spread of the sample, the result is often debatable in applying the method in the field survey. To answer these problems, a survey of rice productivity has been developed through land survey framework approach or the method known as Area Frame Method. The purpose of this survey was to test the frame methodology for measuring frame rice productivity, and compare the results of the survey area rice productivity using area frames with the household listing conducted regularly by the CBS. The development of this method was expected to be used for problems that arise in the current method by considering the geographical conditions, the type of irrigation and government policies in order to increase production. Frame Area method has been tested in Cianjur (in 2012) and Garut (in 2013) in the province of West Java. Number of Mesh (land area 1,000 m x 1,000 m on the map ) in Garut was 120 Mesh. Each mesh was divided into five plots, so that the number of plots in Garut were 600 plots. Selection of sample plots was done by combining Systematic Random Sampling and Simple Random Sampling. The results of the trial method in the area of Garut showed that the productivity of upland and lowland rice were statistically significantly different as well as there were differences in the productivity of irrigated and non-irrigated lands, and there was no difference in the productivity of paddy land as recommended by the government with the conventional. However, the results of statistical tests on rice productivity of Area Method with the official method of CBS in Garut were not significantly different. This may imply that the sample selection method for measuring current productivity (CBS Method) can still be used, but it needs refinement to make the distribution of the samples stratified by altitude, stratification by type of irrigation and by the involvement of farmers who joined a government program